2014
DOI: 10.4238/2014.december.18.19
|View full text |Cite
|
Sign up to set email alerts
|

An economical and combined method for rapid and efficient isolation of fungal DNA

Abstract: DNA isolation is a crucial step of conducting genetic studies in any organism. However, this process is quite difficult when studying fungi because of the need to damage the fungal cell walls of specific structures. In this study, we developed a method for the rapid and efficient isolation of fungal DNA based on simultaneous mechanical and enzymatic cell wall degradation. There are several typical modifications of the standard phenol-chloroform DNA extraction method. This method can be modified to degrade the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Better DNA recovery after lyticase treatment was reported by Karakousis et al [16]. Results from the study by Lech et al showed that double-digestion with two enzymes, lyticase and proteinase K, improved the DNA isolation procedure and shortened the time of incubation with various enzymes [17]. Therefore, for enzymatic cell disruption, the use of two enzymes may be required to achieve an optimal result.…”
Section: Discussionmentioning
confidence: 96%
“…Better DNA recovery after lyticase treatment was reported by Karakousis et al [16]. Results from the study by Lech et al showed that double-digestion with two enzymes, lyticase and proteinase K, improved the DNA isolation procedure and shortened the time of incubation with various enzymes [17]. Therefore, for enzymatic cell disruption, the use of two enzymes may be required to achieve an optimal result.…”
Section: Discussionmentioning
confidence: 96%
“…For DNA isolation, the standard multi-phased phenol-chloroform method proposed by Byrd et al (1990) was used with modifications. The phenol-chloroform method provides satisfactory recovery of DNA from environments such as indoor air, which contain low DNA concentration (Lech et al, 2014). Prepared samples collected from the air were flooded with 400 mL optimized lysis buffer (100 mM EDTA; 100 mM Tris-HCl, pH 8, 0.5 M NaCl; 3% sodium dodecyl sulfate) with the addition of lyticase enzyme (400 U/sample).…”
Section: Dna Extractionmentioning
confidence: 99%